Hepatitis C Virus-Infected Patients Are 'Spared' from the Metabolic Syndrome but Not from Insulin Resistance. A Comparative Study of Nonalcoholic Fatty Liver Disease and Hepatitis C Virus-Related Steatosis. (2009) - Lonardo, Amedeo; Ballestri, Stefano; Adinolfi, Luigi E; Violi, Enrico; Carulli, Lucia; Lombardini, Silvia; Scaglioni, Federica; Ricchi, Matteo; Ruggiero, Giuseppe; Loria, Paola
Abstract : BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) and chronic hepatitis C feature steatosis and insulin resistance (IR), conditions associated with the metabolic syndrome (MS). OBJECTIVES: To assess the prevalence of MS and determinants of IR in patients with NAFLD and chronic hepatitis C. METHODS: Ninety-three consecutive patients with NAFLD, 97 with chronic hepatitis C virus (HCV) genotypes 1 and 2, and 182 'healthy' controls without steatosis were enrolled in the present study. The prevalence of MS was assessed by modified Adult Treatment Panel III criteria and IR by the homeostasis model assessment of insulin resistance (HOMA-IR). IR was defined as the 75th percentile of the HOMA-IR of control subjects. RESULTS: While the prevalence of IR was similar in NAFLD and HCV-infected subjects (70.0% and 78.7%, respectively), the prevalence of MS was significantly higher in NAFLD patients than in HCV-infected patients (27.9% versus 4.1%) and in controls (5.6%). With multivariate analysis, IR was predicted by body mass index (OR 1.263; 95% CI 1.078 to 1.480) and triglyceridemia (OR 1.011; 95% CI 1.002 to 1.020) in NAFLD and by sex (OR for female sex 0.297; 95% CI 0.094 to 0.940) and fibrosis stage (OR 2.751; 95% CI 1.417 to 5.340) in chronic hepatitis C. CONCLUSIONS: IR is independently associated with body mass index and triglyceridemia in NAFLD, sex and fibrosis in chronic HCV infection, and has a higher prevalence in NAFLD and chronic hepatitis C than in controls. However, the frequency of MS in HCV-infected patients, similar to that of controls, is significantly lower than that seen in NAFLD patients. The current diagnostic criteria of MS are more likely to 'capture' patients with NAFLD than with chronic hepatitis C, although both groups are insulin resistant.